SISTEM INFORMASI AKADEMIK BERBASIS WEB PADA UNIVERSITAS WANITA INTERNASIONAL - Nugroho Widyanto (Jurnal Teknologi dan Informasi (JATI), 2018)
Each university has different academic requirements It depends on academic poilicies of each University so that International Women University (IWU) that have purpose to be a centre development technology which competitive, dynamic and inovativ .They can’t manage information well because not been able to take technology properly .Especially at managing student score, student attendance and e-learning for lecturer and student. Of course it will affect toward information and data for IWU stakeholder.We used prototype method as development method.And structured method as approach method. PHP as programming software and MySQL as database to build this Academic Information System.Academic web-based information system created to handle academic problems at IWU especially at student score, student attendance and e-learning for lecturer and student. And advice for next researcher are repairing at interface design ,added application for managing registration for thesis, and application for managing alumnus at this university.